Intracranial Atherosclerotic Stenosis - Jeong Yoon Song; Sun U. Kwon (Cerebrovascular Diseases Extra)
Background: Ischemic stroke is a significant global health problem associated with mortality and disability. Intracranial atherosclerotic stenosis (ICAS) is a leading cause of stroke and contributes to recurrent stroke, especially in the Asian population. ICAS should be distinguished from extracranial atherosclerotic stenosis (ECAS) due to differences in pathophysiology. Understanding the mechanisms of ICAS is crucial for stroke prevention in the Asian population. Traditional vascular risk factors and the degree of the stenosis play an important role in predicting stroke occurrence. Summary: In East Asia, non-atherosclerotic vasculopathies are also often observed in ischemic stroke patients caused by large artery disease, highlighting the importance of identifying the specific etiologies of intracranial artery stenosis. Advances in diagnostic neuroimaging, such as high-resolution MRI (HR-MRI), can be helpful in distinguishing between them. For stroke prevention in patients with both asymptomatic and symptomatic ICAS, intensive management, including strict control of modifiable risk factors and appropriate antiplatelet therapies, is essential. There are no clear guidelines regarding the duration and combination of antiplatelet therapies. However, current recommendations suggest short-term dual antiplatelet therapies for 90 days to reduce the recurrence of stroke in symptomatic severe ICAS (70–99%). Cilostazol is also proposed as a good second-line treatment option, following clopidogrel, which remains the most widely used. In addition, endovascular or surgical interventions could be considered alternatives for a limited subset of symptomatic severe ICAS cases that are hemodynamically unstable. Key Messages: The key messages are as follows: (1) ICAS is a major cause of ischemic stroke, especially in Asian populations. Its distinct pathophysiology, compared to ECAS, requires different treatment strategies for secondary prevention; (2) differentiation of intracranial artery stenosis etiology is essential, and HR-MRI would be a valuable diagnostic tool; (3) stroke prevention includes strict vascular risk factor control and the use of antiplatelet therapies, with short-term DAPT recommended for symptomatic severe ICAS; (4) cilostazol may serve as an effective second-line option for preventing ischemic stroke, while endovascular or surgical interventions may be limited to hemodynamically unstable cases. Background: Ischemic stroke is a significant global health problem associated with mortality and disability. Intracranial atherosclerotic stenosis (ICAS) is a leading cause of stroke and contributes to recurrent stroke, especially in the Asian population. ICAS should be distinguished from extracranial atherosclerotic stenosis (ECAS) due to differences in pathophysiology. Understanding the mechanisms of ICAS is crucial for stroke prevention in the Asian population. Traditional vascular risk factors and the degree of the stenosis play an important role in predicting stroke occurrence. Summary: In East Asia, non-atherosclerotic vasculopathies are also often observed in ischemic stroke patients caused by large artery disease, highlighting the importance of identifying the specific etiologies of intracranial artery stenosis. Advances in diagnostic neuroimaging, such as high-resolution MRI (HR-MRI), can be helpful in distinguishing between them. For stroke prevention in patients with both asymptomatic and symptomatic ICAS, intensive management, including strict control of modifiable risk factors and appropriate antiplatelet therapies, is essential. There are no clear guidelines regarding the duration and combination of antiplatelet therapies. However, current recommendations suggest short-term dual antiplatelet therapies for 90 days to reduce the recurrence of stroke in symptomatic severe ICAS (70–99%). Cilostazol is also proposed as a good second-line treatment option, following clopidogrel, which remains the most widely used. In addition, endovascular or surgical interventions could be considered alternatives for a limited subset of symptomatic severe ICAS cases that are hemodynamically unstable. Key Messages: The key messages are as follows: (1) ICAS is a major cause of ischemic stroke, especially in Asian populations. Its distinct pathophysiology, compared to ECAS, requires different treatment strategies for secondary prevention; (2) differentiation of intracranial artery stenosis etiology is essential, and HR-MRI would be a valuable diagnostic tool; (3) stroke prevention includes strict vascular risk factor control and the use of antiplatelet therapies, with short-term DAPT recommended for symptomatic severe ICAS; (4) cilostazol may serve as an effective second-line option for preventing ischemic stroke, while endovascular or surgical interventions may be limited to hemodynamically unstable cases. Background: Ischemic stroke is a significant global health problem associated with mortality and disability. Intracranial atherosclerotic stenosis (ICAS) is a leading cause of stroke and contributes to recurrent stroke, especially in the Asian population. ICAS should be distinguished from extracranial atherosclerotic stenosis (ECAS) due to differences in pathophysiology. Understanding the mechanisms of ICAS is crucial for stroke prevention in the Asian population. Traditional vascular risk factors and the degree of the stenosis play an important role in predicting stroke occurrence. Summary: In East Asia, non-atherosclerotic vasculopathies are also often observed in ischemic stroke patients caused by large artery disease, highlighting the importance of identifying the specific etiologies of intracranial artery stenosis. Advances in diagnostic neuroimaging, such as high-resolution MRI (HR-MRI), can be helpful in distinguishing between them. For stroke prevention in patients with both asymptomatic and symptomatic ICAS, intensive management, including strict control of modifiable risk factors and appropriate antiplatelet therapies, is essential. There are no clear guidelines regarding the duration and combination of antiplatelet therapies. However, current recommendations suggest short-term dual antiplatelet therapies for 90 days to reduce the recurrence of stroke in symptomatic severe ICAS (70–99%). Cilostazol is also proposed as a good second-line treatment option, following clopidogrel, which remains the most widely used. In addition, endovascular or surgical interventions could be considered alternatives for a limited subset of symptomatic severe ICAS cases that are hemodynamically unstable. Key Messages: The key messages are as follows: (1) ICAS is a major cause of ischemic stroke, especially in Asian populations. Its distinct pathophysiology, compared to ECAS, requires different treatment strategies for secondary prevention; (2) differentiation of intracranial artery stenosis etiology is essential, and HR-MRI would be a valuable diagnostic tool; (3) stroke prevention includes strict vascular risk factor control and the use of antiplatelet therapies, with short-term DAPT recommended for symptomatic severe ICAS; (4) cilostazol may serve as an effective second-line option for preventing ischemic stroke, while endovascular or surgical interventions may be limited to hemodynamically unstable cases. Background: Ischemic stroke is a significant global health problem associated with mortality and disability. Intracranial atherosclerotic stenosis (ICAS) is a leading cause of stroke and contributes to recurrent stroke, especially in the Asian population. ICAS should be distinguished from extracranial atherosclerotic stenosis (ECAS) due to differences in pathophysiology. Understanding the mechanisms of ICAS is crucial for stroke prevention in the Asian population. Traditional vascular risk factors and the degree of the stenosis play an important role in predicting stroke occurrence. Summary: In East Asia, non-atherosclerotic vasculopathies are also often observed in ischemic stroke patients caused by large artery disease, highlighting the importance of identifying the specific etiologies of intracranial artery stenosis. Advances in diagnostic neuroimaging, such as high-resolution MRI (HR-MRI), can be helpful in distinguishing between them. For stroke prevention in patients with both asymptomatic and symptomatic ICAS, intensive management, including strict control of modifiable risk factors and appropriate antiplatelet therapies, is essential. There are no clear guidelines regarding the duration and combination of antiplatelet therapies. However, current recommendations suggest short-term dual antiplatelet therapies for 90 days to reduce the recurrence of stroke in symptomatic severe ICAS (70–99%). Cilostazol is also proposed as a good second-line treatment option, following clopidogrel, which remains the most widely used. In addition, endovascular or surgical interventions could be considered alternatives for a limited subset of symptomatic severe ICAS cases that are hemodynamically unstable. Key Messages: The key messages are as follows: (1) ICAS is a major cause of ischemic stroke, especially in Asian populations. Its distinct pathophysiology, compared to ECAS, requires different treatment strategies for secondary prevention; (2) differentiation of intracranial artery stenosis etiology is essential, and HR-MRI would be a valuable diagnostic tool; (3) stroke prevention includes strict vascular risk factor control and the use of antiplatelet therapies, with short-term DAPT recommended for symptomatic severe ICAS; (4) cilostazol may serve as an effective second-line option for preventing ischemic stroke, while endovascular or surgical interventions may be limited to hemodynamically unstable cases.